What is the actual exposure of organic compounds on Chironomus riparius? - A novel methodology enabling the depth-related analysis in sediment microcosms. (September 2021) - Dorn, Alexander; Hammel, Klaus; Dalkmann, Philipp; Faber, Daniel; Hellpointner, Eduard; Lamshoeft, Marc; Telscher, Markus; Bruns, Eric; Seidel, Erika; Hollert, Henner
Abstract: A novel active sampling method enabled determination of sediment depth profiles revealing the spatial distribution of model compounds N, N-dimethylsulfamide, fluopyram and bixafen (low, medium, high adsorption affinity) in sediment microcosms according to OECD Test 218/219 (Sediment-Water Chironomid Toxicity Test Using Spiked Sediment/Spiked Water). After the overlying water was removed, plastic tubes were inserted into the sediment and the microcosms were frozen. For depth-related analysis, each "sediment core" was mounted in a cutting device and sawed into three 5-mm-slices, respectively (top, middle, bottom). Each slice was centrifuged for sediment and pore water separation. By various sampling dates within 28 days, we could follow the behavior of model compounds depending on sorption affinities and display specific distribution patterns within the sediment. N, N-dimethylsulfamide showing no sediment adsorption, migrated unhindered in (OECD 219) and out (OECD 218) of the sediment via pore water, resulting in homogenous distributions in both test designs. Fluopyram with moderate adsorption affinity revealed a concentration gradient with declining amounts from top to bottom layer (OECD 219) and higher amounts in the middle and bottom layer as compared to the top layer (OECD 218). Bixafen providing a strong adsorption affinity accumulated in the top layer in OECD 219, while no concentration gradients became visible in OECD 218. For establishing a Toxic Substances in Surface Waters (TOXSWA) model, we compared our measurements with simulated results revealing good agreements. The presented methodology is a useful tool to determine more realistic sediment and pore water concentrations, which the Chironomid larvae are exposed to. Graphical abstract: Image 1 Highlights: Active sampling method enables depth related analysis in OECD TG 218/219 systems. Determination of a more realistic concentration to which C. riparius is exposed to. Spatial-temporal distributions of three model compounds were revealed. Development of a TOXSWA model simulating the model compound behavior.